Pertanggungjawaban Pidana Memerintah Mencantumkan Keterangan Palsu Dalam Akta Autentik - Ni Putu Angie Daradinanti; Anak Agung Sagung Laksmi Dewi; Made Minggu Widiantara (Jurnal Preferensi Hukum, 2025)
Criminal liability is a form of determining whether a suspect or defendant is responsible for a crime that has occurred, namely the violation of falsifying a letter or important document as an authentic letter, subject to criminal sanctions. In this regard, what legal provisions relate to the offense of ordering the inclusion of false information in original documents? And what was the judge's opinion when making the decision in case Number 49/Pid.B/2021/PN.Gto? This research uses standard legal methodology by conducting research based on the legal documents used, such as law books and statutory regulations. The results of the study show that the legal provisions regarding the criminal offense of document forgery are regulated in Article 263 of the Criminal Code and Article 266 of the Criminal Code. Article 263 of the Criminal Code regulates document forgery in general (both creating and using forged documents), while Article 266 of the Criminal Code specifically deals with the falsification of information in authentic deeds. The judge's considerations in making a decision are regulated in Article 266 paragraph (1) of the Criminal Code in conjunction with Article 55 paragraph (1) of the Criminal Code, which refers to the criminal act of forging authentic documents (deeds) committed jointly. This article covers perpetrators who order the inclusion of false information in authentic deeds, as well as those who order or participate in such acts.